Determinants of Angola's Parallel Market Real Exchange Rate - Nagayasu, Jun (IMF Working Papers; Working Paper, 1999)
The paper estimates Angola's equilibrium parallel market real exchange rate during the 1992-98 period. Using standard integration/co-integration techniques, the results fail to support the purchasing power parity hypothesis and indicate that two exogenous variables-the price of oil and the foreign interest rate-are able to explain most of the variation in the real exchange rate during the last seven years. These results contrast with the tenet that the parallel market exchange rate in Angola is solely influenced by monetary developments.